Meat yield characteristics of broiler fed different levels of palm oil (Bangladesh Journal of Animal Science, 2014)
Seven hundred fifty day old unsexed broiler chicks were used in a 35-d trial to examine the effect of supplementing different levels of palm oil on lean meat yield of broilers. The chicks were randomly distributed following a completely randomized design in five treatment groups having three replications per treatment. Each treatment had 150 birds with 50 birds per replicate. Five diets were formulated using locally available ingredients as diet without oil, diet containing 2.0%, 3.0%, 4.0% and 5% palm oil. Results indicated that weight gain of broilers differed significantly (p